Floristic richness in catchment areas of Papagini River – a tributary of River Pennar, Andhra Pradesh, India - Kumar, Rajendra (International Journal of Environment, 2014)
A floristic inventory study was carried out in Papagini river basin of Andhra Pradesh during January - December, 2008. Species richness showed 545 species. The family, genera and lifeform dominance were determined by dry climatic conditions of this region, thus makes the dominance of Poaceae, Fabaceae, Euphorbiaceae, Acanthaceae and Asteraceae as family level and Acacia, Euphorbia, Cassia, Commelina and Ficus as genera level. The order of lifeforms dominance was herbs, shrubs, trees, grasses and climbers. Further, the ecosystem functions were inspected and predictions were made on future existence of river ecosystems based on present human interventions. There were possibilities of loss of native vegetation, which impede the river functions and destabilization of ecosystem. Hence, to restore/preserve river basin, the Natural Resources Conservation methods were recommended. DOI: http://dx.doi.org/10.3126/ije.v3i1.9953 International Journal of Environment Vol.3(1) 2014: 177-204